The quest for a circular economy final definition: A scientific perspective - Nobre, Gustavo Cattelan; Tavares, Elaine (Journal of cleaner production, 2021)
Circular Economy (CE) has been one of the most transformational tendencies for the past years. What seemed to be one more organizational hype, is now appearing as a global trend, affecting macro, meso and microenvironments, ranging from governments, global organizations (such as the UN), the whole private sector, science, to final consumers and individuals. Despite the numerous CE definitions, a common sense regarding what CE means is still subject of studies. This opens space for misinterpretation and misuse, as well as greenwashing and image depreciation risks. Consequently, some organizations tend to shape CE to their own definitions and paradigms rather than changing their businesses. This article builds on previous work and aims to establish a common-sense CE definition, separating it from its enablers and related concepts, which seem to be the root causes of misuse. We asked 44 worldwide CE experts PhDs the same question: “Using your own words, please describe what you understand by “Circular Economy”. Database was compiled and analysed through a coded framework and triangulated with the support of R statistical tool. The main outcome is a final definition proposal, along with a structured CE framework. It is expected this research will provide resources to allow standards organizations to establish formal cross-industry CE policies and regulations, leading to scales, targets, KPI's development for CE assessments and audits; and guide organizations and governments on their CE transition roadmaps. •A final Circular Economy statement definition was proposed.•A structured general Circular Economy framework was created.•Researchers and practitioners now have access to CE's What, How, Where and Why.•Circular Economy policies, regulations, scales, KPI's can now be formally developed.